In the equation 6x − 2 = −4x + 2, Spencer claims that the first step is to add 4x to both sides. Jeremiah claims that the first step is to subtract 6x from both sides. Who is correct? Explain.

Respuesta :

Answer:

Both Of Them

Step-by-step explanation:

You can start on either side to solve for x. It will get you the same answer.

Spencer

6x - 2 = -4x + 2

+4x        +4x

10x - 2 = 2

     +2    +2

10x = 4

x = .4 or [tex]\frac{2}{5}[/tex]

Jeremiah

6x - 2 = -4x + 2

-6x        -6x

-2 = -10x + 2

-2            -2

-4 = -10x

x = .4 or [tex]\frac{2}{5}[/tex]

Answer:

Both are true. Both methods will produce the same solution as long as inverse operations and equality properties are used correctly. They are both able to isolate the variable on one side of the equation.

Step-by-step explanation: